Burden, maternal risk factors, and fetal outcomes in twin pregnancies: a retrospective observational study - Banga, Siftie; Naagar, Jagrati K.; Patel, Priyanka; Hajela, Shalini; Mishra, Nitu; Saad, Talha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Twin pregnancies present significant challenges for obstetricians worldwide. Although they account for a relatively small percentage of global births, their occurrence varies across different regions. The increasing utilization of assisted reproduction techniques and the advancing maternal age contribute to the growing incidence of twin pregnancies. As a result, it is essential to understand the implications and risks associated with multiple gestations. The objective was to determine the burden of twin pregnancies, identify maternal risk factors, assess fetal outcomes, and explore potential associations between these factors. Methods: Data were collected from hospital records, including information on maternal age, parity, method of conception, gestational age, pregestational body mass index (BMI), and family history. Maternal and fetal complications, mode of delivery, and high-risk conditions in the fetuses were documented. Statistical analysis was performed using the Fisher-exact test. Results: The study included 78 twin pregnancies. The majority of women (78.2%) fell within the age range of 21-30 years. The majority of women (70.5%) had a normal pregestational BMI. Preterm births occurred in 24.3% of twin pregnancies. Hypertensive disorders (24.0%) and foetal malpresentation (38.0%) were common indications for cesarean section. Fetal complications included intrauterine growth restriction (11.5%), birth weight discordance (25.0%), early neonatal deaths (14.7%), and low APGAR scores (16.0%). Conclusions: Twin pregnancies present challenges due to the increased risks of maternal complications, preterm birth, and adverse fetal outcomes. The study emphasizes the need for careful management and monitoring of twin pregnancies to improve outcomes.